HUBUNGAN ANTARA RASA NYERI DI LEHER DENGAN POSISI MELIHAT DEKAT KETIKA DUDUK MEMBACA, MENULIS DAN MENGGAMBAR - Sofwan, Achmad; Soebijanto, Soebijanto; Soempeno, Bambang (Lembaga Penelitian Universitas YARSI, 2009)
In globalization era, many schools offered integrated school model, among others are full day school, boarding school, etc. which is characterized by longer learning time than that in the public school at the same level. The extra-learning time would eventually prolong the student?s seating time. The chairs are probably comfortable however spinal back pain might be suffered. The cause of spinal back pain (schoolchildren?s neck, shoulder and back) could not be determined accurately. The aim of this study was to investigate the relationship between neck pain and near looking position while they were sitting to read, write and draw. This was a cross sectional study with analytical observation. The subjects of observation were 124 students of Sekolah Dasar Islam Terpadu (SDIT) Lukman Al-Hakim grade VI, with the age range was 10-12 years. The student?s visual activity was examined and flexion angle of the neck were measured while they were sitting to read, write and draw. Questionnaire was used to collect the frequency and the severity of complaints. The statistical methods used were chi-square and discriminant analysis. The result showed that the correlation coefficients between neck pain with near looking position while they were sitting to read, write and draw were 0,671, 0,693 and 0,632 respectively. It was concluded that there was a strong correlation between neck pain and near looking position while they were sitting to read, write and draw.